Effect of Collaborative Concept Mapping Instructional Strategy on Secondary Students’ Achievement in Difficult Biology Concepts - Kyado, Jonah Joel; Abah, Clement O.; Samba, Regina M. A. (American Journal of Social Sciences and Humanities, 2019)
This study investigated the Effects of Collaborative Concept Mapping Instructional Strategy (CCMIS) on the Achievement of Senior Secondary Two (SS2) Students in Perceived Difficult Biology Concepts. The aim of the study was to identify the biology concepts students perceived as difficult and to determine the effects of CCMIS on the mean achievement scores of students in the perceived difficult biology concepts. The study was guided by four research questions and three hypotheses. The study adopted a non-randomized Pretest- Posttest Quasi-experimental design. The sample was 276 SS2 biology students selected from six schools from the three education zones in Taraba State using a multi-stage sampling technique. Intact classes were assigned to the experimental and control groups. Data were generated using Perceived Difficult Biology Concepts Inventory (PDBCI) with a Cronbach’s alpha coefficient of 0.76 and Biology Achievement Test (BAT) with KR20 of 0.87. Mean and standard deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 alpha level of significance. The findings revealed that students exposed to CCMIS attained significantly higher mean achievement scores in BAT than those exposed to Conventional Teaching Strategy (F=60.73, p=0.00). In addition, male and female students taught using CCMIS did not differ significantly in achievement (F=0.35, p=0.56). Based on these findings, the study recommended among others that biology teachers should use CCMIS to teach students in perceived difficult biology concepts.